Morphine withdrawal syndrome: Involvement of the dopaminergic system in prepubertal male and female mice - Diaz, Silvina Laura (2005)
Morphine (MOR) withdrawal signs are more marked in males than in females. Considering that the influence of the dopaminergic system on these differences is unclear, we analyzed dopamine (DA) and dihydroxyphenylacetic-acid (DOPAC) brain levels during naloxone (NAL)-precipitated withdrawal as well as the involvement of D1 and D2 receptors in the expression of MOR withdrawal in either sex. Prepubertal Swiss-Webster mice received MOR (2 mg/kg, i.p.) twice daily for 9 days. On the tenth day, dependent animals received NAL (6 mg/kg, i.p.) after MOR and were sacrificed 30 min later. DA and DOPAC concentrations were determined in different brain areas using HPLC with electrochemical detection. Other pool of mice received either a D1 (SCH 23390; 0.2 mg/kg, i.p.) or D2 (raclopride; 0.3 mg/kg, i.p.) receptor antagonist before NAL and withdrawal signs were evaluated. DA and DOPAC levels only decreased in striatum and cortex of withdrawn males. Conversely, both DA receptor antagonists decreased the expression of MOR withdrawal signs in either sex. The neurochemical sex differences described here could partially explain the behavioral sex differences observed during MOR withdrawal. Additionally, SCH-23390 and raclopride effects suggest an important role of both DA receptors in the expression of MOR withdrawal in males and females.